"I've made that little bit of difference to this child": Therapeutic parent's experiences of trials and triumphs in therapeutic children's homes. (1st October 2020) - Burbidge, Chloe Elizabeth; Keenan, Joseph; Parry, Sarah
Abstract: The workforce caring for children in residential homes are central to the outcomes for the UK's most vulnerable children, although are often overlooked in research. The working practices, skills training, and wellbeing of these practitioners are directly linked to service delivery and the recovery outcomes for the children (e.g., ability to form positive relationships, self-regulate and become stable). This study uses a phenomenological approach to explore practitioners' perspectives and experiences of working in a trauma-informed residential children's service, with the aim of informing and improving working practices. Importantly, this study highlights the risk and protective factors that impact practitioner wellbeing and consequently, service outcomes for staff and children. This qualitative study gathered in-depth ideographic data through twelve individual interviews with practitioners working in Therapeutic Children's Homes, which was then inductively analysed using thematic analysis. Two themes developed from the data: "Reciprocal Restorative Relationships" and "The Self within the System." These themes explore the experiences of therapeutic relationships with the children and the collegiate network; as well as the essential role of supervision, training and emotional support to facilitate positive working practices and practitioner wellbeing. Additionally, a cyclical relationship between service outcomes, practitioner wellbeing and the perceived efficacy of the service emerged. Recommendations for service development and future research are discussed.